Keindahan Gaya Bahasa Al-Qur’an Surat Al-Ghasyiyah Perspektif Fadlil Shalih As-Samirro’i - Nuruddin, Ahmad (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar, Pamekasan, 2023)
This research discusses the beauty of the stylistics of the Qur'an in Surah Al- Ghasyiyah. This research will examine the structure of words, sentences, and expressions contained therein. This study uses a qualitative descriptive research method with literature review as the theoretical basis. The data and data sources that will be used are letters, words, sentences, to expressions that contain errors in the Al-Qur'an Surah Al- Ghasyiyah. The results of this study include a knowledge of some of the beauty of the style of language of the Al-Qur'an Surah Al- Ghasyiyah, which can be seen in terms of word order, choice of diction or words, emphasis on expressions, mentioning and deleting a word or sentence, placing the position between front and back, verse separator words, munasabah between verses and between letters. In this case, the perspective of Fadlil Shalih As-Samirro'i in Surah Al- Ghasyiyah can show harmony between the forms of letters, words, sentences and expressions with the meanings and intentions of the verses in accordance with interpretation studies. So that we can know in detail the beauty of uslub from the verses of the Qur'an from a linguistic point of view and from the point of view of interpretations of the Qur'an.